'Honesty matters': an analysis of prevalence and seriousness of academic dishonesty among college students / Imelia Laura Daneil, Parmjit Sing Aperapar Singh and Jacqueline Susan Rijeng - Daneil, Imelia Laura; Aperapar Singh, Parmjit Singh; Rijeng, Jacqueline Susan (2014)
Being honest is really matters to all college students regardless of their fields of studies. Academic dishonesty is no longer an isolated issue but has developed into global concern. Significantly, statistical findings reported by recent studies show an increasing occurrence of cheating as compared to yesteryears. Driven by this interest, this study investigated college students' perceptions towards the prevalence of academic dishonesty at one of the Malaysia colleges. More specifically, this study examined college students' perceptions of acts of academic dishonesty from various perspectives including the seriousness of academic dishonesty. This study employed a purely quantitative method research design which entailed research instrument which is questionnaire. The study involved a total of 96 college students from different semesters and CGPAs. The findings revealed that although the students generally have low prevalence of academic dishonesty, a zero tolerance is expected to be found. Findings indicated that cheating on quiz is more prevalence as compared to cheating on exam, cheating on coursework (i.e. assignment) and plagiarism. Thus, it is recommended that institution should work collaboratively to facilitate student orientations and academic integrity to advocate for the culture of academic integrity.